2009
DOI: 10.4102/ojvr.v76i2.49
|View full text |Cite
|
Sign up to set email alerts
|

<i>Curtisia dentata</i> (Cornaceae) leaf extracts and isolated compounds inhibit motility of parasitic and free-living nematodes

Abstract: Haemonchus contortus and Trichostrongylus colubriformis are among the most important parasitic nematodes of small ruminants. Caenorhabditis elegans, a free-living nematode, is used as a model for evaluating anthelmintic activity of a variety of test substances. Extracts of several medicinal plants are useful in vitro and in vivo against nematode development. Extracts of Curtisia dentata, a South African medicinal plant, and compounds isolated from leaves of this plant were investigated for anthelmintic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…The occurrence of changes that comprise the activity of these enzymes can reduce the hatching rate (Rogers and Brooks, 1977). BA showed no ovicidal action; however, a study by Shai et al (2009) demonstrated that this acid inhibited motility around 75% of L3 larvae of H. contortus in the same concentration used in the present work. The HE, which has BA among other compounds, showed less activity on eggs compared to AE and CE.…”
Section: Ovicidal Activitymentioning
confidence: 76%
See 2 more Smart Citations
“…The occurrence of changes that comprise the activity of these enzymes can reduce the hatching rate (Rogers and Brooks, 1977). BA showed no ovicidal action; however, a study by Shai et al (2009) demonstrated that this acid inhibited motility around 75% of L3 larvae of H. contortus in the same concentration used in the present work. The HE, which has BA among other compounds, showed less activity on eggs compared to AE and CE.…”
Section: Ovicidal Activitymentioning
confidence: 76%
“…The determination of the concentrations used was based on results from pilot experiments, and were well-defined concentrations of 0.8; 1.2; 1.8; 2.7; and 4 mg / mL for extracts and fractions. The concentrations of BA (1.0, 0.75 and 0.5 mg / mL) were defined based on a study by Shai et al (2009). In the 1 mg / mL of BA, the study showed action on larvae of H. contortus.…”
Section: Egg Hatch Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Haemonchus contortus and Trichostrongylus colubriformis are listed among the top ten of most important ruminant's parasites [5][6][7]. Haemonchus contortus causes anaemia, haemorrhagic gastroenteritis, hypoproteinemia partly manifested as submandibular oedema 'bottle jaw' and sudden death [8].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to immersion, direct bioautography is performed without agar: immediately before use, microorganisms are usually transferred from their solid culture medium to a sterile fresh broth containing all required nutrients for proper microbial growth and having a viscosity compatible with spraying if necessary. After appropriate incubation, zones of growth inhibition are observed naturally for spore-producing fungi and pigmented bacteria or revealed via tetrazolium salts ( Figure 4) (Shai et al, 2009). An alcoholic solution can be subsequently sprayed onto the entire layer to fix microorganisms.…”
Section: Direct Tlc Bioautographymentioning
confidence: 99%